A study of Geomagnetic Field and It’s secular variation at the Location Brazilian Anomaly (25Â°S, 45Â°W). - AI-Mahdi, H.A.; Mokheber, A.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
ln this paper we study and analysis the total intensity (P) .and the horizontal component (H) of the geomagnetic field at the location na ly Brazilian Anomaly (Lat 25S, long 4SÂ·"W) in which the geomagnetic field intensity has a minimum value. We examine the relationship. between the F , H) with altitude at a certain latitude, and .relationship between ( F,H ) with the latitude at the certain altitude .We study also the nature of the secular variation of the geomagnetic field at the same locat.ion dpning one century (1900-2000) , we found that the rate of change of field inten5ity (F). is roughly (9.3 % per century). The geomagnetic field data is obtained by using JGRF1 0 model at Brazilian anomaly (long 45"W).